Respon Perkecambahan Tanaman Cabai Rawit (Capsium frutescens L.) dengan Pemberian Berbagai Zat Pengatur Tumbuh Alami - Emilda Emilda; Sofwatun Nida Mursid; Netty Demak H Sitanggang (JURNAL ILMIAH AGRINECA, 2023)
This study aims to determine the effect of soaking the seeds of cayenne pepper (Capsicum frutescens L.) on various natural growth regulators on their germination. The research was carried out in the Jaticempaka experimental garden, Bekasi City. The research design used was a completely randomized design (CRD) consisting of 5 treatments and 4 replications, namely: P0 (water), P1 (coconut water), P2 (shallot extract), P3 (bean sprout extract), and P4 (Gibberellins 21 ppm). The parameters measured in this study were time and germination viability, plant height, leaf length and number of leaves. The results of the observations were analyzed using a one-way ANOVA test with a significance level of 5% and if they were significantly different,continued with a LSD test. The results of the analysis showed that soaking the seeds with Gibberellin resulted in the fastest germination time, which was an average of 60 hours after seedling. Furthermore, treatment P1 is coconut water with an average time of 66 hours. The effect of seed soaking with growth regulators was not significantly different at 7 days after planting (DAP), but at 14 and 21 DAP there was a significant difference in P4, namely soaking with synthetic Gibberellin as shown by the LSD test results. There were no significant differences in the parameters of length and number of leaves found in all treatments and the age of observation. This is presumably due to the lack of growth regulators concentration and soaking time. However that of all the growth regulator treatments given, the treatment with coconut water (P1) showed better results than the other treatments even though the results were not optimal.